The Natural History and Treatment of Meningiomas: An Update - Nyalundja, Arsene Daniel; Mugisha, Fabrice; Karekezi, Claire (Seminars in Neurology, 2023)
Meningiomas are the most frequent nonmalignant tumors of the central nervous system (CNS). Despite their benign nature and slow-growing pattern, if not diagnosed early, these tumors may reach relatively large sizes causing significant morbidity and mortality. Some variants are located in hard-to-access locations, compressing critical neurovascular structures, and making the surgical management even more challenging. Although most meningiomas have a good long-term prognosis after treatment, there are still controversies over their management in a subset of cases. While surgery is the first-line treatment, the use of fractionated radiotherapy or stereotactic radiosurgery is indicated for residual or recurrent tumors, small lesions, and tumors in challenging locations. Advances in molecular genetics and ongoing clinical trial results have recently helped both to refine the diagnosis and provide hope for effective biomolecular target-based medications for treatment. This article reviews the natural history and current therapeutic options for CNS meningiomas.
Keywords: meningioma; central nervous system; tumor; surgery; natural history